SignQuiz: A Quiz Based Tool for Learning Fingerspelled Signs in Indian Sign Language Using ASLR - Jestin Joy; Kannan Balakrishnan; M. Sreeraj (IEEE Access, 2019)
Sign Language is one of the media of communication for deaf people. One should learn sign language to interact with them. Learning usually takes place in peer groups. There exist very few study materials for sign learning. Because of this, the process of learning sign language learning is a difficult task. Fingerspelled sign learning is the initial stage of sign learning and moreover, are used when no corresponding sign exists or signer is not aware of it. Most of the existing tools for sign language learning use external sensors which are costly. This paper discusses SignQuiz, which is a cost-effective web-based fingerspelled sign learning application for Indian sign language (ISL) utilizing automatic sign language recognition technique. SignQuiz helps to learn signs without any external help. This is the first attempt in ISL for learning finger spelled signs using a deep neural network. The results indicate that SignQuiz is better than the printed medium for fingerspelled sign learning.